Evaluation of the effects of implementing a diode transmission device into the clinical workflow. (December 2020) - Paxton, Adam B.; Sarkar, Vikren; Kunz, Jeremy N.; Szegedi, Martin; Zhao, Hui; Huang, Y. Jessica; Nelson, Geoff; Rassiah, Prema; Su, Fan-Chi Frances; Salter, Bill J.
Highlights: The Delta 4 Discover diode transmission detector's effects were evaluated. Effects on beam characteristics, IMRT QA, MV imaging, and superficial dose studied. The effects the Discover has on the beam were found to be minimal. Attention is needed in developing new clinical workflows for safe implementation. Abstract: Purpose: This work investigated effects of implementing the Delta 4 Discover diode transmission detector into the clinical workflow. Methods: PDD and profile scans were completed with and without the Discover for a number of photon beam energies. Transmission factors were determined for all beam energies and included in Eclipse TPS to account for the attenuation of the Discover. A variety of IMRT plans were delivered to a Delta 4 Phantom+ with and without the Discover to evaluate the Discover's effects on IMRT QA. An imaging QA phantom was used to assess the detector's effects on MV image quality. OSLDs placed on the Phantom+ were used to determine the detector's effects on superficial dose. Results: The largest effect on PDDs after dmax was 0.5%. The largest change in beam profile symmetry and flatness was 0.2% and 0.1%, respectively. An average difference in gamma passing rates (2%/2 mm) of 0.2% was observed between plans that did not include the Discover in the measurement and calculation to plans that did include the Discover in the measurement and calculation. The Discover did not significantly change the MV image quality, and the largest observed increase in the relative superficial dose when the Discover was present was 1%. Conclusions: The effects the Discover has on the linac beam were found to be minimal. The device can be implemented into the clinic without the need to alter the TPS beam modeling, other than accounting for the device's attenuation. However, a careful workflow review to implement the Discover should be completed.